Dynamic 18F-FET PET/CT to differentiate recurrent primary brain tumor and brain metastases from radiation necrosis after single-session robotic radiosurgery - Winna Lim; Gueliz Acker; Juliane Hardt; Markus Kufeld; Anne Kluge; Winfried Brenner; Alfredo Conti; Volker Budach; Peter Vajkoczy; Carolin Senger; Vikas Prasad (Cancer Treatment and Research Communications, 2022)
Objective: Cyberknife robotic radiosurgery (RRS) provides single-session high-dose radiotherapy of brain tumors with a steep dose gradient and precise real-time image-guided motion correction. Although RRS appears to cause more radiation necrosis (RN), the radiometabolic changes after RRS have not been fully clarified. 18F-FET-PET/CT is used to differentiate recurrent tumor (RT) from RN after radiosurgery when MRI findings are indecisive. We explored the usefulness of dynamic parameters derived from 18F-FET PET in differentiating RT from RN after Cyberknife treatment in a single-center study population. Methods: We retrospectively identified brain tumor patients with static and dynamic 18F-FET-PET/CT for suspected RN after Cyberknife. Static (tumor-to-background ratio) and dynamic PET parameters (time-activity curve, time-to-peak) were quantified. Analyses were performed for all lesions taken together (TOTAL) and for brain metastases only (METS). Diagnostic accuracy of PET parameters (using mean tumor-to-background ratio >1.95 and time-to-peak of 20 min for RT as cut-offs) and their respective improvement of diagnostic probability were analyzed. Results: Fourteen patients with 28 brain tumors were included in quantitative analysis. Time-activity curves alone provided the highest sensitivities (TOTAL: 95%, METS: 100%) at the cost of specificity (TOTAL: 50%, METS: 57%). Combined mean tumor-to-background ratio and time-activity curve had the highest specificities (TOTAL: 63%, METS: 71%) and led to the highest increase in diagnosis probability of up to 16% p. – versus 5% p. when only static parameters were used. Conclusions: This preliminary study shows that combined dynamic and static 18F-FET PET/CT parameters can be used in differentiating RT from RN after RRS.